THE FILLING OF PRATAMA HIGHER LEADERSHIP POSITIONS TO STRENGTHEN BUREAUCRACY REFORM IN THE PERSPECTIVE OF PERFORMANCE RESPONSIBILITY OF THE STATE CIVIL APPARATUS IN BATAM CITY COVERNMENT - Fadlan; Zudan Arif Fakrulloh; Faisal Santiago (Mimbar Hukum, 2023)
Abstract The purpose of this article is to analyze the position of the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform (Menpan-RB) Number 13 of 2014 concerning Procedures for Filling High Leadership Positions in the Hierarchy of Legislation, and to criticize the mechanism and implementation of the fulfillment process of the Primary Leadership Position (JPT) and building a Bureaucratic Model used by the State Civil Apparatus (ANS) to promote the Performance Accountability Perspective to improve Good Governance and Clean Government. In order to answer the aim of the study, we used a combination of the normative "legal research" approach and the empirical "juridical sociological" approach using descriptive analysis, which aims to obtain a comprehensive description or general description and describe the facts related to general bureaucracy policies, especially the position. This study found that the Regulation of the Ministry of Empowerment of State Administrative Reform Bureaucratic Reform Number 13 of 2014 concerning Filling Certain Structural Positions in Government Agencies has not been binding from the perspective of legal system accountability; thus, it is feared that there may be a lawsuit dispute in the State Administration against officials who have participated in the selection of Position Filling of the High Leadership Position (JPT) Pratama. Abstrak Tujuan artikel ini adalah menganalisis kedudukan Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi (Menpan-RB) Nomor 13 Tahun 2014 tentang Tata Cara Pengisian Jabatan Pimpinan Tinggi Dalam Hierarki Peraturan Perundang-undangan, dan mengkritisi mekanisme dan pelaksanaan proses pemenuhan Jabatan Pimpinan Utama (JPT) dan membangun Model Birokrasi yang digunakan Aparatur Sipil Negara (ANS) untuk mendorong Perspektif Akuntabilitas Kinerja guna meningkatkan Good Governance dan Clean Government. Untuk menjawab tujuan penelitian, kami menggunakan gabungan antara pendekatan “penelitian hukum” normatif dan pendekatan “yuridis sosiologis” empiris dengan menggunakan analisis deskriptif, yang bertujuan untuk memperoleh gambaran menyeluruh atau gambaran umum serta menguraikan fakta-fakta yang berkaitan dengan hal tersebut. kebijakan birokrasi secara umum, khususnya jabatan. Penelitian ini menemukan bahwa Peraturan Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Nomor 13 Tahun 2014 tentang Pengisian Jabatan Struktural Tertentu pada Instansi Pemerintah belum mengikat dari sudut akuntabilitas sistem hukum; Sehingga dikhawatirkan akan terjadi sengketa gugatan di lingkungan Tata Usaha Negara terhadap pejabat yang mengikuti seleksi Pengisian Jabatan Pimpinan Tinggi (JPT) Pratama.